An investigation of the role of wild rats in transmitting Leptospira spp. to stray cats and dogs in Malaysia - Muhd, Zafirah; Khor, Kuan Hua; Alashraf, Abdul Rahman; Lau, Seng Fong; Radzi, Rozanaliza; Bejo, Siti Khairani; Hashim, Rohaidah (SAGE Publications Inc., 2025)
Stray cats and dogs have been reported to shed Leptospira spp., and wild rats are speculated to be involved. We aimed to elucidate the role of wild rats in transmitting Leptospira to stray cats and dogs in Malaysia. We tested sera from 124 wild rats with the microscopic agglutination test (MAT): 88 of 122 (72%) sera were positive (titer ≥1:100), with the predominant serovars Icterohaemorrhagiae, Bataviae, Ballum, Javanica, Lai, and Pomona. With a Leptospira-specific PCR assay, we detected pathogenic Leptospira spp. in 33 of 124 (27%) kidney samples and 13 of 79 (16%) urine samples. Isolates obtained by culture of rat kidney and urine were identified to the species level with MAT using hyperimmune sera and the PCR assay. From 29 isolates, 2 pathogenic species were identified: L. interrogans serovar Bataviae and L. borgpetersenii serovar Javanica. Phylogenetic analysis using partial 16S rDNA sequences of the Leptospira spp. from the wild rats indicated that the species were similar to isolates from stray cats and dogs in previous studies. We confirmed that wild rats carried pathogenic Leptospira spp. and were a potential source of leptospiral infection of stray cats and dogs in Malaysia.